Enzyme‐PISA: An Efficient Method for Preparing Well‐Defined Polymer Nano‐Objects under Mild Conditions - Tan, Jianbo; Xu, Qin; Li, Xueliang; He, Jun; Zhang, Yuxuan; Dai, Xiaocong; Yu, Liangliang; Zeng, Ruiming; Zhang, Li (Macromolecular rapid communications., 2018)
Enzyme catalysis is a mild, efficient, and selective technique that has many applications in organic synthesis as well as polymer synthesis. Here, a novel enzyme‐catalysis‐induced reversible addition‐fragmentation chain transfer (RAFT)‐mediated dispersion polymerization for preparing AB diblock copolymer nano‐objects with complex morphologies at room temperature is described. Taking advantage of the room‐temperature feature, it is shown that pure, worm‐like polymer nano‐objects can be readily prepared by just monitoring the viscosity. Moreover, it is demonstrated that inorganic nanoparticles and proteins can be loaded in situ into vesicles by this method. Finally, a novel oxygen‐tolerant RAFT‐mediated dispersion polymerization initiated by enzyme cascade reaction that can be carried out in open vessels is developed. The enzyme‐initiated RAFT dispersion polymerization provides a facile platform for the synthesis of various functional polymer nano‐objects under mild conditions. A novel enzyme‐catalysis‐induced reversible addition‐fragmentation chain‐transfer‐mediated dispersion polymerization is developed for preparing AB diblock copolymer nano‐objects with complex morphologies at room temperature. This method provides a facile platform for the synthesis of various functional polymer nano‐objects under mild conditions.